# mathematics plz need help sir steve

Given
Given

f1(x,y)=x^4y^3
f2(x,y)=5x^7+sin(3y)

find the determinant
step plz full step

1. 👍 0
2. 👎 0
3. 👁 110
1. Do you mean the Jacobian?

F1x = 4x^3y^3
F1y = 3x^4y^2
F2x = 35x^6
F2y = 3cos(3y)

So, the determinant of J(f1,f2,x,y) is

(4x^3y^3)(3cos(3y))-(35x^6)(3x^4y^2)
= 12x^3y^3 cos(3y) - 105x^10y^2

See

http://www.wolframalpha.com/input/?i=jacobian+of+(x%5E4y%5E3,+5x%5E7%2Bsin(3y))

1. 👍 0
2. 👎 0

## Similar Questions

1. ### math

An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

2. ### math

Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

3. ### Calculus

Use the four-step process to find the slope of the tangent line to the graph of the given function at any point. f(x) = 16 - 10 x Step 2: f(x + h) - f(x) = Step 4: f'(x) = lim(h->0)(f(x + h)- f(x))/h =

4. ### math

10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use

1. ### MATH

Hannah is showing her work in simplifying (6.1 − 4.5) − 2.5 + 3.9. Identify any error in her work or reasoning. Step 1: (6.1 − 4.5) − 2.5 + 3.9 Step 2: 6.1 + (− 4.5 − 2.5) + 3.9 (associative property) Step 3: 6.1 − 7

2. ### maths sir steve help~reiny

sin(πcosx)-cos(πsinx)=0 then find sin2x step plz

3. ### math

An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

4. ### Help PLZ!!

consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: -4 3 7 + 7 + (-3 4 7 ) Step 1: = -4 3 7 + (-3 4 7 ) + 7 Step 2: = -4 + (- 3 7 ) + (-3) + (- 4 7 ) + 7 Step 3: = -4 + (- 3 7 ) + (-

1. ### ALGEBRA HELP

When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

2. ### Quick math help

In which step below does a mistake first appear in simplifying the expression? 0.5(-12c+6)-3(c+4)+10(c-5) Step 1: -6c+3-3(c+4)+10(c-5) Step 2: -6c+3-3c-12+10(c-5) Step 3: -6c+3-3c-12+10c-50 Step 4: 7c-41 Please help me!!! Thank

3. ### trig

Verify the identity sin 3x cos 3x = 1/2 sin 6x can you show step by step please

4. ### Algebra

Debbie finished her algebra test early so she decided to check each of her answers. After checking her answer to question #10, she realized she made a mistake in her solution. In which step does Debbie make her mistake? Original